Expression of Genes 1-deoxy-D-xylulose 5-phosphate Reductoisomerase (DXR), Sabinen Synthase (Tctps1) and α- terpineol Synthase (Tctps5) and its Relation to Thymol and Carvacrol Biosynthesis in Thymus vulgaris under Water Deficit Stress - F Mirzaei; F Fatehi; A Ismaili; A Yaghotipoor; A Qaderi (Institue of Medicinal Plants, ACECR, 2017)
Background: Thymol and Carvacrol are the two important secondary metabolites from Thymus vulgaris that productions of them are controlled by genetic and environmental factors. Objective: Evaluation of Water stress effects on expression of three important genes of thymol and carvacrol biosynthetic pathway and also physiological and phytochemical properties of Thymus vulgaris. Methods: The present study was conducted in a randomized complete block design with 4 treatments and 3 replications in Institute of Medicinal Plants, ACECR, Karaj.  For this purpose, the treatments were selected as control (FC), 70% of FC, 40% of FC, and 20% of FC. Gene expression was studied using real-time PCR method, and HPLC was applied to essence analysis. Also physiological characteristic including chlorophyll content, relative water content, electrolyte leakage percentage and carotenoids content were analyzed. Results: The results revealed that water stress significantly influenced the gene expression (P≤ 0.05). The highest gene expression of DXR and Tctps5 was observed in 70% of FC, while the highest one of TvTPS1 was recorded in 40% of FC. Moreover, the maximum thymol and carvacrol was found in 70% of FC. In other hand the highest chlorophyll content and corotenoids content were obtained in 100% and 70% of FC respectively. Also there were not significant differences between treatments for  relative water content and electrolyte leakage percentage. Conclusion: The 70% of FC through influencing of genes in the firs and last of MEP pathway increased thymol and carvacrol production.